Analisis kesalahan paragraf dalam menulis karangan deskripsi peserta didik kelas VI pada pembelajaran bahasa Indonesia - Febriyanti Diah Kusumaning Dewi; St. Y Slamet; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2023)
This study aims to describe paragraph errors in the description essay. Paragraph errors in the form of, (1) Element completeness errors, (2) Unity errors, and (3) Cohesion errors. Then the most dominant error and the cause of paragraph errors in the description essay of grade VI elementary school. This research is qualitative descriptive research, the subjects in this study were sixth grade students. Data collection using document studies and interviews. The validity test technique used is triangulation of sources and techniques. The technical data analysis used is the analysis of Tarigan-language fragments. The results of this study are as follows. Element completeness errors were found to be 48.56%, unity errors of 25.44%, and cohesiveness errors of 25.83%. The most dominant error is the error of elemental completeness. Factors causing paragraph errors caused by students include: lack of student interest in Indonesian language, especially writing and reading, lack of vocabulary, and low motivation of students to learn Indonesian. While the factors that come from the class teacher are in the form of choosing inappropriate learning models or strategies, delivery that is only fleeting in a short time.